Differences in Art Appreciation in Autism: A Measure of Reduced Intuitive Processing. - Brosnan, Mark; Ashwin, Chris (Journal of Autism & Developmental Disorders, 2023)
Art appreciation reflects an initial emotional and intuitive response to artwork evaluation, although this intuitive evaluation can be attenuated by subsequent deliberation. The Dual Process Theory of Autism proposes that individuals with Autism Spectrum Disorder (ASD) have a greater propensity to deliberate and reduced intuition compared to matched controls. Evaluations of high- and low-quality artworks were undertaken by 107 individuals with a diagnosis of ASD and 145 controls. Controls consistently evaluated high-quality artworks to be much better quality than the low-quality artworks, reflecting intuitive processing. The ASD sample showed a reduced difference in evaluations between high- versus low-quality artwork, which reflects reduced intuitive processing and greater deliberative processing and is consistent with predictions by the Dual Process Theory of Autism.